Analysis of the Physicochemical Properties, Replication and Pathophysiology of a Massively Glycosylated Hepatitis B Virus HBsAg Escape Mutant - Md. Golzar Hossain (MDPI AG, 2021)
Mutations in HBsAg, the surface antigen of the hepatitis B virus (HBV), might affect the serum HBV DNA level of HBV-infected patients, since the reverse transcriptase (RT) domain of HBV polymerase overlaps with the HBsAg-coding region. We previously identified a diagnostic escape mutant (W3S) HBV that produces massively glycosylated HBsAg. In this study, we constructed an HBV-producing vector that expresses W3S HBs (pHB-W3S) along with a wild-type HBV-producing plasmid (pHB-WT) in order to analyze the physicochemical properties, replication, and antiviral drug response of the mutant. Transfection of either pHB-WT or W3S into HepG2 cells yielded similar CsCl density profiles and eAg expression, as did transfection of a glycosylation defective mutant, pHB-W3S (N146G), in which a glycosylation site at the 146aa asparagine (N) site of HBs was mutated to glycine (G). Virion secretion, however, seemed to be severely impaired in cases of pHB-W3S and pHB-W3S (N146G), compared with pHB-WT, as determined by qPCR and Southern blot analysis. Furthermore, inhibition of glycosylation using tunicamycinTM on wild-type HBV production also reduced the virion secretion. These results suggested that the HBV core and Dane particle could be formed either by massively glycosylated or glycosylation-defective HBsAg, but reduced and/or almost completely blocked the virion secretion efficiency, indicating that balanced glycosylation of HBsAg is required for efficient release of HBV, and mutations inducing an imbalanced glycosylation of HBs would cause the virion to become stuck in the cells, which might be associated with various pathogeneses due to HBV infection.